Bacteriological Profile and Antibiotic Susceptibility Pattern of Isolates in Neonatal Sepsis : Antibiotic Susceptibility Pattern of Neonatal Sepsis - Ehsan, Shaista; Marium, Roohiya (Pakistan Journal of Health Sciences, 2023)
Sepsis in newborns is a serious medical condition having a high mortality. Pakistan and other developing countries have a high burden of neonatal sepsis. Objectives: To determine the bacterial spectrum and antibiotic activity pattern in neonatal sepsis. Methods: This retrospective cross-sectional research was performed at the Pediatrics Unit of Ziauddin University Hospital Karachi from 1st June 2022 till 1st December 2022. A total of 120 medical records of neonates admitted with the clinical suspicion of sepsis were reviewed. Non-probability convenience sampling technique was used. Data regarding clinical characteristics of neonates, type of bacteria isolated and antibiotic susceptibility results were recorded. SPSS version 20 was used for statistical analysis. The results were written as frequencies / percentages. Results: Neonatal sepsis was suspected in 120 newborns but blood culture-proven infection was present in 32 (13.3%) neonates with 23(71.8%) having early -onset sepsis. The mean age on admission was 7.61±3.61 days. Acinetobacter was the commonest bacteria implicated in sepsis followed by Klebsiella ,Burkholderia and Serratia. The mortality rate in study population was 8.3%. Mortality was highest in Klebsiella sepsis. None of the bacterial species were sensitive to ampicillin while Acinetobacter and Burkholderia species responded to colistin, polymyxin and meropenem but showed resistance to imipenem. Conclusion: Early-onset neonatal sepsis has a high prevalence especially with gram -negative bacteria. Antimicrobial resistance to first line empiric therapy is common